2010
DOI: 10.1111/j.1445-5994.2009.02144.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxicity with 5‐fluorouracil and capecitabine: more than just vasospastic angina

Abstract: In this case series we present a variety of different cardiac toxicities with 5-fluorouracil and its pro-drug capecitabine, including myocardial infarction, cardiomyopathy, sinoatrial and atrioventricular node dysfunction, takotsubo cardiomyopathy and QT prolongation with torsade-de pointes ventricular tachycardia. We stress the fact that while vasospasm is a well-recognized side-effect of this class of chemotherapeutic agent, broader cardiotoxicity is commonly seen and an increased awareness of the range of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(75 citation statements)
references
References 14 publications
0
69
0
6
Order By: Relevance
“…5-Fluorouracil and its prodrug capecitabine can cause vasospasm-induced chest pain, 19,20 with a rarer incidence for paclitaxel, tamoxifen, and first-generation TKIs. 11 The risk of cardiovascular ischemic events for some second-generation TKIs is alarmingly high.…”
Section: Mechanisms Of Cardiotoxicitymentioning
confidence: 99%
“…5-Fluorouracil and its prodrug capecitabine can cause vasospasm-induced chest pain, 19,20 with a rarer incidence for paclitaxel, tamoxifen, and first-generation TKIs. 11 The risk of cardiovascular ischemic events for some second-generation TKIs is alarmingly high.…”
Section: Mechanisms Of Cardiotoxicitymentioning
confidence: 99%
“…Significant prolongation of QTc intervals and frequent ventricular arrhythmias have also been found on Holter monitoring associated with 5-FU infusion [37]. A review of 22 patients demonstrated significant early prolongations of the QT interval which persisted throughout the duration of chemotherapy [40] and another case series described QT prolongation with torsade de pointes in a patient receiving 5-FU infusions [5].…”
Section: Arrhythmiamentioning
confidence: 99%
“…Acute coronary syndrome (ACS) precipitated by the administration of 5-FU is a rare but well-established phenomenon [1,2] and only one of several adverse cardiac effects related to this chemotherapeutic agent. Additional cardiotoxic effects include cardiomyopathy, vasospastic angina, coronary thrombosis and dissection, malignant arrhythmias, and sudden cardiac death [3][4][5][6][7]. Furthermore, following any cardiac complication, it is essential to weigh the risks of repeat drug administration against the potential for cure of the malignancy given this agent's proven efficacy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cardiotoxic effects of these drugs seem to be multifactorial [16]. The suggested phenomenon of vasospasm induced by 5-FU or capecitabine cannot explain the possibility of cardiomyopathy, sinoatrial and atrioventricular node dysfunction, takotsubo cardiomyopathy, and QT prolongation with torsade de pointes ventricular tachycardia [17]. Although a recent European Society of Cardiology statement on cardiovascular toxicity of cancer treatment emphasises the ischaemic effect of 5-FU [18], cardiotoxicity of pyrimidines seems to have numerous mechanisms, including apoptosis of myocardium, depletion of high-energy phosphate compounds, increased oxygen consumption, impaired antioxidant defence system, and more [16].…”
Section: Discussionmentioning
confidence: 99%